Contralesional distractors enhance ipsilesional target processing after right-hemispheric stroke. (May 2016) - Vossel, Simone; Fink, Gereon R.
Abstract: Stroke can result in marked impairments in the processing of information presented in contralesional space. The present prospective study investigated how a contralesional distractor affects ipsilesional perception in patients with a right-hemispheric stroke. In a simple target detection task, the influence of the distractor on reaction times (RTs) was examined in stroke patients and compared to the performance of healthy elderly controls. Distractor interference effects were related to measures of neglect and extinction using a regression analysis. Moreover, the magnitude of the behavioural distractor effect entered a voxel-based lesion-symptom mapping (VLSM) analysis with the hypothesis that parietal and temporoparietal lesions are related to altered distractor processing. While the presence of a distractor in the opposite hemifield slowed down RTs in healthy controls for left and right targets, this effect was only observed for contralesional left targets in the group of right-hemispheric patients. In stark contrast, the presence of a distractor in the contralesional hemifield expedited ipsilesional (i.e., right) target detection. This effect was significantly related to lesions in the anterior middle temporal and temporoparietal cortex, external and internal capsule, as well as the superior longitudinal fascicle (SLF). These results elucidate the nature of the disruption of attentive processing in the contralesional hemifield after right-hemispheric stroke. More specifically, they shed light on the abnormal prioritisation of ipsilesional information: our data suggest that damage to the temporal and temporoparietal cortex and white matter tracts may transform contralesional stimulation into an unspecific saliency signal contributing to facilitated information processing in ipsilesional space.